Narcodiplomacy: exporting the US war on drugs - Friman, Henry Richard (Cornell University Press, 1996)
If illicit drug trafficking is a global problem, why won't other nations comply with the drug control agenda of the United States? NarcoDiplomacy departs from traditional responses to this question, which have held that compliance with the American agenda has been beyond the capacity of key countries. By focusing on Germany and Japan, touted as two of the strongest allies of the United States in drug control efforts, H. Richard Friman exposes the flaws in capacity arguments and the policies based on them.